The spaces of Southeast Asian scholarship - Mojares, Resil B. (2013)
This professorial address argues that the genealogy of Southeast Asian studies must be traced to the work carried out by Southeast Asians themselves in the context of the practice and formation of local or national scholarship. The argument is illustrated by the historical formation of what can be called “Southeast Asian studies” in the Philippines. The paper was a keynote address that was read at the conference on “Engaging the Classics in Malay and Southeast Asian Studies,” Singapore, 17–18 June 2010, sponsored by the Institute of Southeast Asian Studies and the national University of Singapore’s Department of Malay Studies.
Keywords: Southeast Asia -- Study and teaching; Malays (Asian people) -- Study and teaching; Learning and scholarship